Method of Determining the Enterprise Development based on Recourses/Competences Importance – Competitive Potential Matrix - Konieczna, Izabela (Organizacja i Kierowanie, 2025)
The aim of the article is to propose a method of determining the company’s development basing on the recourses/competences importance – competitive potential matrix (RP matrix) from which top managers can find out on which stage of development is their company. The matrix has a special value and is a source of important information in case of checking the organization development in comparison to past years. The matrix can also be useful when the company wants to find out if the changes the company has made are sufficient in improving company’s development or it needs to make more changes in business model to reach the desired level of development. Another application of the matrix is its usage in preventive checking of the way of development or maintaining a certain previously set level. Empirical verification of organization development changes was developed on the basis of results of direct interviews conducted with representatives of the senior management of dairy cooperatives from Świętokrzyskie Voivodship with the help of interview questionnaire. Analysis of the data showed that all analyzed cooperatives were in the “extraordinary development” field of the matrix before and after 3 years. Compared to the base year, the cooperatives improved their position, which may indicate the correct development path chosen by the management.